Section Editor's Notes. - Oster, Robert A. (American Statistician, 2011)
An introduction is presented in which the editor discusses various reports within the issue on topics such as an accuracy comparison among six spreadsheets including Microsoft Excel, OpenOffice Calc, and Gnumeric, and the comparison of the software procedures for linear mixed models.